Enhancing electrochemical performance of LiFePO4 by vacuum-infiltration into expanded graphite for aqueous Li-ion capacitors. (1st November 2017) - Qin, Chuanli; Li, Yawen; Lv, Shixian; Xiang, Junyu; Wang, Chenlong; Zhang, Xugang; Qiu, Shen; Yushin, Gleb
Abstract: Olivine-type LiFePO4 (LFP) is one of the most widely utilized cathode materials for high power Li-ion batteries (LIBs). In spite of rapidly growing popularity of LIBs, the rate performance of the highest power LFP cells is still insufficiently high for some high-power applications. In this work we demonstrate that vacuum-infiltration of LFP precursors into pores of low-cost expanded graphite (EG), an in-situ sol-gel process, followed by calcination, allows formation of LFP/EG nanocomposites that demonstrate remarkable performance in higher power Li-ion capacitor (LIC) applications. Such composites comprise spherical LFP particles embedded into EG pores and additionally wrapped by EG films, forming a highly efficient and stable conducting network. Such a morphology greatly accelerates Li-ion diffusion and improves Li-ion exchange between LFP and electrolyte. As a result, compared to commercial LFP particles of comparable size, the optimized LFP/EG nanocomposite shows significantly higher rate performance, dramatically better stability and higher specific capacitance of up to about 1200 F g −1 . The use of environmentally friendly, safe and low-cost aqueous electrolyte is particularly advantageous for LIC applications that are cost-sensitive and require enhanced safety. Our results demonstrate a great promise of our approach, which is additionally applicable for a broad range of other intercalation chemistries.